A Study: Active Factors of SMEs on Youth Community in Gelam Jaya Village, Tangerang Regency - Rini Novianti; Tri Anggraeni; Sonny Santosa (eCo-Buss, 2021)
Covid-19 pandmic has hit almost all countries in the world. It also causes economic turbulence, including in Indonesia. Effects caused by this Covid-19 pandemic are perceived by all business sectors, including SMEs. This research was aimed at to find out the effects of Covid-19 pandemic on SMEs located in Gelam Jaya Village, one of villages in Tangerang Regency. Members of society from all levels complained over the effects caused by this pandemic. Employees lost their jobs, people lost their family members as they suffered from this Covid-19, the enterpreneurs encountered deep decrease on their turnover, and SMEs underwent decreases in their sales and many of them had to stop operating their business. The decresing sales volume undergone by SMEs may be caused several factors, they were Sales Methods, Product Types, Promotion, and Distribution. In Covid-19 pandemic time, face-to-face sales were hard to conduct. The products considered to sell by the SMEs were basic needs which last long. Still, both promotion and distribution channels were interrupted by this pandemic. This is a quantitative research. The research was conducted by spreading questionnaires to SMEs located in Gelam Jaya Village. The data were later processed by using SPSS of 18 version. Thus, this research was aimed at finding what factors could be stimulants for youth community. So, they would be interested in entrepreneurship in order to develop economy in the middle of the pandemic. This research applied survey method within quantitative as its approach. There were 169 people from youth community in Gelam Jaya Village, Tangerang Regency. The method to process the data was factor analysis. The results of the research showed that the factor of ‘Availability of Mentoring/Debriefing Routines for Enterpreneurship’ (VAR00006) belonged to the first group and scored above 0.5. This means there were influences between the finished Mentoring/debriefing on introduction to AVP (availability, visibility, and promotion) strategy in the process of manifesting entrepreneurship or opening SMEs in the middle of this pandemic.